HYDROPHILIC NANOSILICA DERIVED FROM FLY ASH AND BOTTOM ASH: A SUSTAINABLE APPROACH FOR ENHANCED OIL RECOVERY - Prayoga, Muhammad Dzikri; Ikhwanuddin, Ikhwanuddin (Jurnal Geosaintek, 2026)
Silica-based nanoparticles synthesized from fly ash and bottom ash (FABA) have been investigated as potential agents for Enhanced Oil Recovery (EOR). The utilization of solid waste generated from coal-fired power plants not only mitigates environmental impacts but also provides value-added functional materials. This article examines the strategic potential of fly ash and bottom ash (FABA)-derived nanosilica as a low-cost and environmentally sustainable alternative material for EOR applications. The discussion integrates sustainability perspectives with EOR performance by positioning FABA-based nanosilica as a technically feasible and environmentally viable green material. By synthesizing key findings from recent literature, this paper highlights the relationship between the physicochemical properties of nanosilica, nanofluid stability, and the dominant EOR mechanisms, including wettability alteration, interfacial tension reduction, contact angle measurement, viscosity factor, porosity modification, and structural disjoining pressure. These findings indicate that silica nanofluids derived from FABA exhibit significant potential for practical implementation in Enhanced Oil Recovery (EOR), while simultaneously offering a sustainable approach to industrial waste management and long-term energy resilience.